sanirizaçãp e refrigeração de ovos de codornas comercias contaminados experemente por Salmonella Typhimurium - LACERDA, Maria Juliana Ribeiro (2011)
The objective of this study was to verify the physical, chemical and microbiological quality of Japanese quail eggs artificially contaminated with Salmonella Typhimurium, sanitized and stored at different temperatures (between 5 and 25 ºC) for 27 days. We used 768 eggs with opaque shells (Experiment 1) and bright shells (Experiment 2) with typical pigments of the species and average weight of 11 g. The experimental design was completely randomized in a 2x2x2 factorial arrangement (contamination x sanitation x cooling) with six replications, with one egg per experimental unit. The eggs were contaminated by handling with 1.5 x 105 colony forming unit (CFU) of Salmonella Typhimurium / mL and according to the treatments, sanitized with 5ppm Cl a solution, and stored at 5 or 25 ° C. The physical (egg weight, specific gravity, shell thickness, yolk, albumen and shell ratio, Haugh unit, yolk albumen index), chemical (pH of yolk and albumen) and bacteriological (bacterial count in eggshell and egg content) qualities were analyzed. Results of Experiment 1 showed a inear regression of sorage time (P <0.05) of storage time (up to 27 days) worsening the variables of egg weight, albumen and yolk index and albumen ratio. A quadratic effect (p <0.05) of storage time worsening the pH of albumen and Haugh units. There was an interaction for the yolk pH variable between sanitation and refrigeration (p <0.05) after 27 days, while those for non refrigerated eggs the best result was for sanitized eggs, showing the importance of sanitization. In Experiment 2 (eggs with bright shells) there was a linear effect (P <0.05) of storage time (27 days), worsening the variables of egg weight, albumen ratio and Haugh units and quadratic effects (p <0.05) worsening albumen index and pH. These results indicate that eggs with opaque or bright, had a poorer quality with increasing internal storage time, especially at 25 ° C. Quail eggs with opaque or bright shell, stored up to 27 days, should be sanitized (5 ppm of chlorine) and cooled to 5 ° C during storage to maintain physical and chemical qualities, regardless of bacterial contamination. The sanitization (5 ppm Cl) and cooling (5 º C) are effective in reducing the growth of Salmonella in experimentally infected quail eggs.